Meningkatkan Kualitas Nasionalisme Generasi Millenial Indonesia untuk Meminimalisasi Pengaruh Derap Era Globalisasi Informasi - Munir, Nur (LP3M STIT Al Urwatul Wutsqo Jombang, 2024)
This research examines strategies to deal with the influence of information globalization on the nationalism of Indonesia's millennial generation. Using a qualitative literature study method, this research analyses the challenges and opportunities in maintaining the spirit of nationalism in the digital era. The results show the importance of a comprehensive approach that includes strengthening national resilience in the aspects of ideology, politics, economy, socio-cultural, and defense and security (Ipoleksosbudhankam). The main strategies include reforming the education system with the integration of nationalist values, optimizing the role of mass media, establishing a cyber war force, and increasing patriotism programs that focus on the millennial generation. The research emphasizes the importance of balancing openness to global information flows with the maintenance of national identity. In conclusion, the synergy between government policies, educational institutions, and community participation is needed to build strong national resilience in facing the challenges of information globalization, while maintaining and enhancing the spirit of nationalism among Indonesia's young generation. The implementation of this strategy is expected to strengthen Indonesia's position in facing increasingly complex global dynamics while maintaining the fundamental values of Pancasila and the 1945 Constitution